Learning To Read And Write The Koran For Children In Sukasari Village, Arahan District, Indramayu Regency - Didik Himmawan; Dewi Fitriani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The development of village potential towards a progressive society is something that must be considered. Students are expected to be able to understand every problem that occurs in society and make the best decisions to be able to solve these problems with creative ideas. Sukasari Village is one of the village areas located in Arahan District, Indramayu Regency. The majority of the eyes of the Sukasari people are as farmers. As for some of the potential of Sukasari Village, namely agriculture, animal husbandry and home industry. One form of student contribution in fostering community togetherness. “Learning to Read and Write the Qur'an for Children”. The aim of implementing the program is to increase understanding, belief and apply religious values ​​in daily life for children -children in Sukasari Village. This program uses several methods such as the demonstration method, question and answer, or the Iqro method when reciting the Koran. The porporation method, a summary of the material to be delivered, then students listen and understand then the essence that has been conveyed by the educator. While the question and answer method is used when teaching and learning activities take place and there are students who do not understand, then students are welcome to ask questions and educators will answer. Not only asking the educator, but students are able and allowed to ask other students so that there is active interaction during the learning process. Meanwhile, the Iqro method is used when carrying out recitation training, especially for children who are still illiterate with hijaiyah letters.